Frontiers of (Pareto) Optimal and Sustainable Water Management for Hydropower and Ecology - Perona, Paolo; Niayifar, Amin; Schwemmle, Robin; Razurel, Pierre; Flury, Reto; Winz, Elias; Barry, D. A. (Frontiers in Environmental Science, 2021)
River regulation alters the natural flow regime of streams with consequent impacts on terrestrial and aquatic habitats of the riparian zone. The severity of such impacts can be modulated by changing the redistribution rules at water intakes and reservoirs. Contrary to minimal-flow policies, non-proportional and proportional redistribution policies result in variable environmental flow releases, namely Dynamic Environmental Flows (DEFs), which improve the global (i.e., ecological and economic) efficiency of water use practice, e.g., for energy production. DEF assessment is based on different indicators. However, the choice and aggregation method of different hydrological and fish habitat indicators affects the assessment of the global power plant performance, i.e., the frontier of efficient solutions (sensu Pareto). This study investigates DEF assessment, and shows the extent to which the choice and method of aggregation of different indicators impacts the frontier of Pareto-efficient solutions. The findings are supported by six case studies of hydropower practice that differ in terms of river morphology, energy production amount and technique. The relative importance of several types of indicators is examined as is their influence on optimal and sustainable water allocation solutions that lie on the Pareto frontier. The analysis shows that DEFs arising from either proportional or non-proportional redistribution rules can positively impact strategies of sustainable management of freshwater resources.